Comparação entre os métodos DGA online e laboratorial para avaliação do estado de óleos minerais em transformadores de potência - SOUSA, Marcino Assunção Leite de (2023)
In this work we present a study of monitoring and diagnosis of the oil insulation system of power transformers, carried out via the DGA-online and laboratory method. Based on the data collected through the evaluation of the state of the power transformers, comparisons were made between the methods, with the objective of qualitatively verifying which one would produce greater efficiency, due to its simplicity and low cost. With the justification of monitoring and maintaining the quality of the insulating oil, to extend the useful life of the equipment and guarantee the reliable performance of the system, this study aimed to establish criteria to qualify the condition and criticality of the transformers, through the comparison between data obtained in laboratory, and through the CALISTO 5 system.